THE EFFICACY OF PANCHTIKTAGHRIT GUGGLU AND SHIRISHADI LEPA IN THE MANAGEMENT OF MANDAL KUSHTH W.S.R TO TINEA CORPORIS - Sharma, Bhawana (International Journal of Ayurveda and Pharma Research, 2018)
Skin is one of the five ‘Gyanindriyas’ as described in Ayurvedic texts. It is responsible for ‘Sparsh Gyan’ or touch sensation; therefore it plays a great role in physical and mental health of any individual. It is most affected by fungal infections. According to modern science the fungal infections caused by dermatophytes are called as dermatophytosis. Tinea or Ringworm infection presents with of the circular skin lesions with elevated edges. In Ayurveda, all skin diseases have been discussed under the broad heading of Kushta. The study comprised of a series of 10 patients of Mandal kushta. The patients were selected from OPD and IPD of Kayachikitsa of Sri Krishna Ayurvedic Medical College, Varanasi. In the present study a clinical trial is done with trial drug Panchtiktkta ghrit gugglu and external application of Shirisadi lepa. Panchtiktkta ghrit gugglu is cited from Bhaishajya Ratnavali and Shirisadi lepa is cited from Charak Samhita. Panchtiktkta ghrit gugglu is given in a dose of 2 tablets 3times in a day with the combination of external application of Shirisadi lepa twice in a day for 45 days. Three follow ups with duration of 15 days were done. A remarkable changes were found in various sign and symptoms based on assessment criteria which are Kandu (itching), Sotha (inflammation), Srava (secretions), Vivarnata (discolouration) and Vrana (lesion). It was indeed a proper and suitable approach for this chronic skin disorder as the patients of Mandal Kustha combat a lot for this dreadful disease as it persists for long time and spread rapidly.